2018
DOI: 10.4236/gep.2018.61008
|View full text |Cite
|
Sign up to set email alerts
|

A Geospatial Analysis of Mycenaean Habitation Sites Using a Geocumulative versus Habitation Approach

Abstract: In this study GIS and spatial analysis were applied in order to thoroughly examine possible relationships between the location of Mycenaean (16 th -11 th c. BC) settlements in Messenia and the geomorphological characteristics of the area of their establishment. The idea lying behind this attempt is that the Mycenaeans would not have established their habitation sites randomly but according to decisive criteria, among which geomorphological characteristics played an important role. Such criteria include land as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 13 publications
(9 reference statements)
0
8
0
Order By: Relevance
“…Regarding the climatic factor, by examining the soil reports it was observed that the majority of the 140 habitation sites that examining in this paper (Malaperdas and Zacharias 2018) are located in generally southern orientations, resulting in conditions of maximum sunshine; these orientations also ensure protection from the cold, strong north winds. For the verification of the results, the wind intensity parameter prevailing in the locations was examined in correlation to the parameters of solar radiation and thermal load, for both the directness of the solar input entering the site and the cumulative effect that it may have regarding the orientation (McCune 2007).…”
Section: Methodology Advantages Versus Older Habitation Modelsmentioning
confidence: 90%
“…Regarding the climatic factor, by examining the soil reports it was observed that the majority of the 140 habitation sites that examining in this paper (Malaperdas and Zacharias 2018) are located in generally southern orientations, resulting in conditions of maximum sunshine; these orientations also ensure protection from the cold, strong north winds. For the verification of the results, the wind intensity parameter prevailing in the locations was examined in correlation to the parameters of solar radiation and thermal load, for both the directness of the solar input entering the site and the cumulative effect that it may have regarding the orientation (McCune 2007).…”
Section: Methodology Advantages Versus Older Habitation Modelsmentioning
confidence: 90%
“…(Murrieta-Flores 2010). For example, in the case of agricultural societies (Roebuck 1945), (Arapogianni and Kakouros 2016) breeding zones can be supported up to two hours away from the main settlement (Malaperdas and Zacharias 2018). In the case of Ancient Thouria, the city was built and flourished close to rich clean water sources, Pamissos and Aris Rivers to the west as well as Xerilas closer to the east.…”
Section: Methodology and Analysismentioning
confidence: 99%
“…In recent studies, more attention is given to local topography of a region while approaching site allocation or landscape topographic patterns in settlement selection (De Reu et al 2011). On that note, determining locations of archaeological sites or materials through human activity and occupational behaviour (Judge and Sebastian 1988b) is a continuous procedure that integrates various scientific aspects (Vines and St 2012) (Malaperdas and Zacharias 2018). To support the development of such models or patterns documenting and examining environmental, geographic and geological conditions in known archaeological sites is important for establishing pattern criteria.…”
Section: Introductionmentioning
confidence: 99%
“…Major infrastructure projects probably facilitated this expansion, for example, the partial drainage of the Kopaïs basin (Aravantinos et al 2006;Lane et al 2016Lane et al , 2020 and possibly also of the Nemea Valley (Cherry and Davis 2001). The most important of these settlements, socially and politically, are located on either flat ground or small hills (up to 300 m), which combine easy access to the surrounding land and defensibility (Malaperdas and Zacharias 2018).…”
Section: Settlement Patterns and Demographymentioning
confidence: 99%